Directionality of corticomuscular coupling in essential tremor and cortical myoclonic tremor. Issue 8 (August 2021) - Sharifi, S.; Luft, F.; Potgieter, S.; Heida, T.; Mugge, W.; Schouten, A.C.; Bour, L.J.; van Rootselaar, A.F.
Highlights: Renormalized partial directed coherence is a suitable approach to investigate corticomuscular directionality in tremor. An efferent cortical drive is lacking in the majority of essential tremor (ET) patients; corticomuscular coupling in ET has predominantly an afferent direction. ET might be associated with a non-linear (rate-dependent) cortical transmission. Abstract: Objective: A role of the motor cortex in tremor generation in essential tremor (ET) is assumed, yet the directionality of corticomuscular coupling is unknown. Our aim is to clarify the role of the motor cortex. To this end we also study 'familial cortical myoclonic tremor with epilepsy' (FCMTE) and slow repetitive voluntary movements with a known cortical drive. Methods: Directionality of corticomuscular coupling (EEG-EMG) was studied with renormalized partial directed coherence (rPDC) during tremor in 25 ET patients, 25 healthy controls (mimicked) and in seven FCMTE patients; and during a self-paced 2 Hz task in eight ET patients and seven healthy controls. Results: Efferent coupling around tremor frequency was seen in 33% of ET patients, 45.5% of healthy controls, all FCMTE patients, and, around 2 Hz, in all ET patients and all healthy controls. Ascending coupling, seen in the majority of all participants, was weaker in ET than in healthy controls around 5–6 Hz. Conclusions: Possible explanations are that tremor in ET results from faulty subcortical output bypassing the motor cortex; rate-dependent transmission similar to generation of rhythmic movements; and/or faulty feedforward mechanism resulting from decreased afferent (sensory) coupling. Significance: A linear cortical drive is lacking in the majority of ET patients.